Movin’ on Up: Socioeconomic Mobility and the Risk of Delivering a Small-for-Gestational Age Infant - Slaughter-Acey, Jaime C. (Matern Child Health J, 2016)
OBJECTIVE: Poor fetal growth is associated with increased rates of adverse health outcomes in children and adults. The social determinants of poor fetal growth are not well understood. Using multiple socioeconomic indicators measured at the individual level, this study examined changes in maternal socioeconomic position (SEP) from childhood to adulthood (socioeconomic mobility) in relation to poor fetal growth in offspring. METHODS: Data were from the Pregnancy Outcomes and Community Health (POUCH) Study (September 1998–June 2004) that enrolled women in mid-pregnancy from 52 clinics in five Michigan communities (2,463 women: 1824 non-Hispanic White, 639 non-Hispanic Black). Fetal growth was defined by birthweight-for-gestational age percentiles; infants with birthweight-for-gestational age <10(th) percentile were referred to as small-for-gestational age (SGA). In logistic regression models, mothers whose SEP changed from childhood to adulthood were compared to two reference groups, the socioeconomic group they left and the group they joined. RESULTS: Approximately, 8.2% of women (non-Hispanic White: 6.3%, non-Hispanic Black: 13.9%) delivered an SGA infant. Upward mobility was associated with decreased risk of delivering an SGA infant. Overall, the SGA adjusted-odds ratio was 0.34 (95% Confidence Interval [CI]: 0.17-0.69) for women who moved from lower to middle/upper vs. static lower class, and 0.44 (CI: 0.28-1.04) for women who moved from middle to upper vs. static middle class. There were no significant differences in SGA risk when women were compared to the SEP group they joined. CONCLUSIONS: Our findings support a link between mother's socioeconomic mobility and SGA offspring. Policies that allow for the redistribution or reinvestment of resources may reduce disparities in rates of SGA births.